Peran Enzim Ca2+ - ATPase pada Membran Sel Darah Merah - Ferry P. Gultom (Faculty of Dentistry, Universitas Indonesia, 2015)
Ca2+ - ATP ase enzyme is transmembrane protein which is found in membrane cell. This protein works as a pump in many cases such as thalassemia which causes leakage of the cell as there is oxidation of sulphidril chain from amino acid in membrane. The calcium-ion intake must be pumped out to get red blood cell homeostatic condition. The aim of this paper is to determine the activity of Ca2+ - ATPase enzyme as a pump of Ca ion in membrane cell.